Magnetic Retraction of Bowel by Intraluminal Injectable Cyanoacrylate-Based Magnetic Glue. (12th November 2013) - Wang, Zhigang; Brown, Andrew; André, Pascal; Brown, Stuart I.; Florence, Gordon J.; Cuschieri, Alfred
Abstract : Magnetic retraction offers advantages over physical retraction by graspers because of reduced tissue trauma. The objectives of this study are to investigate a novel method of magnetisation of bowel segments by intraluminal injection of magnetic glue and to demonstrate the feasibility of magnetic retraction of bowel with sufficient force during minimal access surgery. Following an initial materials characterisation study, selected microparticles of stainless steel (SS410- μ Ps) were mixed with chosen cyanoacrylate glue (Loctite 4014). During intraluminal injection of the magnetic glue using ex vivo porcine colonic segments, a magnetic probe placed at the injected site ensured that the SS410- μ Ps aggregated during glue polymerisation to form an intraluminal mucosally adherent coagulum. The magnetised colonic segments were retracted by magnetic probes (5 and 10 mm) placed external to the bowel wall. A tensiometer was used to record the retraction force. With an injected volume of 2 mL in a particle concentration of 1 g/mL, this technique produced maximal magnetic retraction forces of 2.24 ± 0.23 N and 5.11 ± 0.34 N (n = 20 ), with use of 5 and 10 mm probes, respectively. The results indicate that the formation of an intraluminal coagulum based on SS410- μ Ps and Loctite 4014 produces sufficient magnetic retraction for bowel retraction.